Makna, Arti dan Hakikat Filsafat Ilmu (Studi Literatur) - Oktavia, Lidya Fransiska; Yovica, Alia; Fatrisna, Yuli; Mudarti, Hasni; Jamilus, Jamilus (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to find out the meaning, meaning and essence of philosophy of science. This study uses literature study methods to collect and analyze various relevant theoretical and empirical sources. The sources studied include scientific journals, books, and articles related to the topic of meaning, meaning, and essence of the philosophy of science. Critical analysis of the existing literature is carried out to evaluate gaps in previous research and propose new perspectives that are more relevant to current scientific developments. The results of the analysis show that Philosophy of Science plays an important role in providing a theoretical framework that underlies scientific research and theoretical evaluation. The philosophy of science not only serves as a theoretical reflection on science, but also as a concrete guide in the development and application of knowledge. By providing criticism, methodological framework, and ethical insights, philosophy of science contributes greatly to pushing science to be more accurate, responsible, and relevant to human life